Optimal Trade-In and Pricing Strategy under Strategic Consumers and Sequential Innovation - Xue Yang; Xiaofeng Liu (Discrete Dynamics in Nature and Society)
With the growing emphasis on the advancement of the circular economy, companies are investigating various approaches, such as trade-in strategies, to stimulate consumption and support the circular economy. Although there is a substantial amount of research on trade-ins, there is a scarcity of multistrategy studies on upgrade programs. In order to address this deficiency, we created four two-period dynamic game models that utilize strategic consumer and product sequential innovation as the basis for examining company pricing and strategic decision-making. Our research shows that a single rollover upgrade program can generate significant revenues when there is a high level of product innovation and consumers are strategic in their decision-making. On the other hand, a dual rollover upgrade program can target a bigger range of customers who are looking to replace their current products. If the product is not highly innovative or strategically important for consumers, the profit advantage of the upgrade program with a single rollover is lost. In such cases, the upgrade program with a dual rollover not only ensures revenue but also helps to increase the size of the customer group who are more willing to replace their products.